2014
DOI: 10.1002/jcph.282
|View full text |Cite
|
Sign up to set email alerts
|

Baseline and new‐onset morphologic ECG abnormalities in healthy volunteers in phase I studies receiving placebo: Changes over a 6‐week follow‐up period

Abstract: Morphological ECG abnormalities occur in 5-12% healthy adults participating in early phase clinical trials. We retrospectively analyzed 16,472 12-lead ECGs recorded at multiple time points in 420 volunteers (282 males, 138 females; aged 18-76 years) randomized to receive placebo from 19 Phase I studies to see if some baseline ECG abnormalities may disappear or new abnormalities may appear during the study. One hundred forty-four (34.3%) subjects had abnormal baseline ECGs, of which 66 (44.8%) reverted to norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
4
10
0
2
Order By: Relevance
“…During 24-h ambulatory ECG recordings, Stinson et al observed normal sinus rhythm in only 13% of 156 healthy volunteers throughout the entire observation period [14] . In one striking example from a case report, an idiosyncratic ventricular rhythm was found under placebo medication during a double-blind phase I study [15] .…”
Section: Discussionmentioning
confidence: 99%
“…During 24-h ambulatory ECG recordings, Stinson et al observed normal sinus rhythm in only 13% of 156 healthy volunteers throughout the entire observation period [14] . In one striking example from a case report, an idiosyncratic ventricular rhythm was found under placebo medication during a double-blind phase I study [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Whether these arrhythmias are due to the investigational new drug or are a normal occurrence can be interpreted only if the background prevalence of the arrhythmia in healthy individuals is well documented. Some previous studies have documented prevalence of arrhythmias in 10‐second ECGs from healthy volunteers in clinical trials . However, there are very sparse data in literature on the prevalence of arrhythmias on 24‐hour continuous ECGs in healthy volunteers from clinical trials .…”
mentioning
confidence: 99%
“…Some previous studies have documented prevalence of arrhythmias in 10-second ECGs from healthy volunteers in clinical trials. [11][12][13][14] However, there are very sparse data in literature on the prevalence of arrhythmias on 24-hour continuous ECGs in healthy volunteers from clinical trials. [7][8][9] We therefore studied the prevalence of various cardiac arrhythmias in 24-hour continuous ECG recordings in a large number of healthy subjects participating in phase 1 clinical trials.…”
mentioning
confidence: 99%
“…при записи ЭКГ у 420 здоровых волонтеров. Частота ЖЭ в этом исследовании составила 1%, наджелудочковая экстрасистолия (НЖЭ) была выявлена в 3,8% случаев [14]. Аналогичные результаты были получены и в ряде других исследований [20,21].…”
Section: распространенность нарушений ритма сердца в популяцияхunclassified
“…Интерес к этой проблеме сохраняется на протяжении длительного времени, однако отсутствие единых методологических подходов, а также использование в большинстве исследований однократной регистрации электрокардиограммы (ЭКГ), малоинформативного метода выявления аритмий делают результаты исследований посвященных изучению распространенности НРС весьма противоречивыми [13,14].…”
Section: Introductionunclassified